Mobile Technological Apps to Improve Frontal Lobe Functioning - Ramos-Galarza, Carlos (2021)
The technological proposal here elaborated consists of a cellphone app denominated Mind & Brain which encompasses subcomponents that allow the compensation of each frontal lobe function. In the component of planning, for example, this application allows a person to have an electronic diary to set daily activities to accomplish and will have the opportunity to set reminders and alarms with the patient´s own voice about the activities that must achieve in that specific day. For emotional regulation, the person will be able to be in control of every emotion and reaction. In monitoring, the subject must follow verbal instructions to solve successfully a problem, previously inserted. For decision making, the app will identify the possible consequences of choosing one or another option. With this technological innovation, people with any frontal lobe disorder will improve their quality of life.